The Urgency of Legal Pluralism in Addressing Early Marriage in Indonesia - Pertiwi, Endah Mustika; Surya Sukti; Mustar (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2025)
Legal pluralism lives in the midst of Indonesian society to this day, this condition is because Indonesian society still upholds customary norms and religious norms. This diversity has an impact on the benchmark for a person's maturity to enter into marriage. Each region has a different interpretation of the age and conditions for marriage. This research aims to see the urgency of legal pluralism to address the phenomenon of early marriage that still occurs due to various aspects of life. This research uses normative juridical method, which is a research method of principles and theories with data obtained from various data in the form of books, journals, documents, and relevant information to support the scientificity of this research. The results of this study are, 1) The high rate of early marriage is caused by hereditary conditions, low education, passive parents, and the influence of the local environment. 2) The urgency of legal pluralism is very important to address this phenomenon, because Indonesia is filled with three pillars of law, custom, religion, and law. In order to reach an agreement, legal pluralism is enforced.